Experimental investigation for the local scour around V-shaped spur-dikes - Layth Abdul Rasool ALASADI; Tagreed Hameed KHLIF; Fadhel Abdulabbas HASSAN (Przegląd Naukowy Inżynieria i Kształtowanie Środowiska, 2023)
Spur-dikes are efficient hydraulic structures that are made for numerous purposes. They have one end on the stream bank and another extending into the current. As a result of the existing spur-dikes in the stream course, the local scour phenomena usually occur around them, leading to several predicaments which have been of great concern to the hydraulic engineers. For the present work, laboratory experiments were carried out to measure the scour depths around several spur-dikes located at different distances for the V-shaped one. The experiments were conducted using physical models installed in a non-curved flume with a bed with uniform cohesion-less sediment of a medium particle size (d50 = 0.7 mm). All the models were operated under the subcritical flow of clear-water conditions. The investigations include three spur-dikes (1, 2 and 3) and three distances between them (1, 1.5 and 2 of spur-dike length) as two countermeasures to minimize the local scour depths. The results showed that an increasing number of spur-dikes and the distances between them would decrease the scour depths within the limit of the present study. The experimental data were used to create a new formula of R2 = 0.954 that reflects a good agreement with the experimentally observed results.